Cork extractives exhibit thermo-oxidative protection properties in polypropylene–cork composites and as direct additives for polypropylene. (June 2015) - Aroso, Ivo M.; Fernandes, Emanuel M.; Pires, Ricardo A.; Mano, João F.; Reis, Rui L.
Abstract: The thermo-oxidative stability of polypropylene (PP) in composites containing 15 wt.% of cork and the performance of selected cork extracts as stabilizing additives for PP was evaluated by Oxidation Induction Time (OIT) and by Oxidation Onset Temperature (OOT). The results showed that cork increases the OIT of PP in the composite and it was identified that the cork extractives fraction is responsible for such behavior. Selected cork extracts with high antioxidant capacity (determined by dpph radical scavenging and oxygen reactive absorbance capacity assays) were compounded by extrusion with PP in 0.5 and 1.5 wt.%. It was found that the ethanol extract is the most effective as thermo-oxidative stabilizer for PP. At the loading level of 1.5%, the OIT increases from 3.8 (neat PP) to 29.7 min at 200 °C and from 1.2 (neat PP) to 9.0 min at 220 °C. The OOT also increases from 216 °C (neat PP) to 247 °C. Mechanical tests, performed on PP loaded with the cork extracts, showed that the presence of these extracts has no significant effect on the polymer mechanical performance. The results demonstrate the suitability of cork as a source of thermo-oxidative stabilizing additives for the formulation of polyolefins, and enable the exploitation of new routes of cork valorization.